PELAKSANAAN BIMBINGAN KELOMPOK DI MADRASAH ALIYAH SWASTA AL WASLIYAH GADING DI KOTA TANJUNG BALAI - Rizki Ananda Putri; Saiful Akhyar Lubis; Budiman Budiman (UIN Sumatera Utara Medan, 2019)
The purpose of this research is to know the program and implementation of group coaching in the city of Madrasah Aliyah Al Washliyah private Tanjungbalai.This research is backed by the interest of researchers to examine the process of implementing the group guidance at private Madrasah Aliyah Alwashliyah Gading Kota Tanjungbalai. The method used in this study is qualitative in the type of research method of phenomenon (phenomenology), because all who want to be researched are sourced from a deep interview to the object or informant in the research, observation directly and documentation.The results of the research from the implementation of group guidance in private Madrasah Aliyah Alwashliyah town Tanjungbalai is: The first implementation of group guidance is one of the Guidance and Counseling programs in the group guidance service. Secondly, Of in the implementation of the group's guidance is implemented in a programmatic or asynchronous basis between theory with the implementation of Group guidance services.